The Role of Financial Technology in Micro, Small and Medium Enterprises in Financial Innovation and Social Change - Tiva Nur Fathonah; Rahmat Agus Santoso (Universitas Muhammadiyah Gresik, 2022)
Background – The application of technology is a challenge for MSME to survive in the current era. The main fuction of using technology is to make it easier for evryone to make transactions. Rapid technology development can change the industry as financial technologhy (fintech). With the presence of fintech in the economic enviroment, it can provide new knowledge regarding financial literacy. Objectives – This research aims to analyze the role of financial techonology to micro, small, medium enterprises in financial literacy in the Kebomas Subdistrict, Gresik. Design/ Methodology/ Approach – This qualitatif is with research of checking the validity of the data uses the member check Findings - The results The result of this research found that micro, small, medium enterprises (MSMEs) get convenience in saving activities, save time in saving, and security through digital payment applications. MSMEs also make it easier to manage finances to find out business benefits and can develop their business. Research Implications – This research can be used as a MSME to advance business in the 4.0. Research Limitations - Research conducted by MSME who have not used digital payments bacause many MSME are unable to keep up with modern times.